2021
DOI: 10.1091/mbc.e20-06-0390
|View full text |Cite
|
Sign up to set email alerts
|

The TIM22 complex mediates the import of sideroflexins and is required for efficient mitochondrial one-carbon metabolism

Abstract: Acylglycerol Kinase (AGK) is a mitochondrial lipid kinase that contributes to protein biogenesis as a subunit of the TIM22 complex at the inner mitochondrial membrane. Mutations in AGK cause Sengers syndrome, an autosomal recessive condition characterized by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy and lactic acidosis. We mapped the proteomic changes in Sengers patient fibroblasts and AGKKO cell lines to understand the effects of AGK dysfunction on mitochondria. This uncovered downr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 65 publications
(121 reference statements)
1
31
0
Order By: Relevance
“…In this report, authors observed that the yeast mitochondrial pyruvate carrier, which has an odd number of transmembrane segments and a matrix-facing N-terminus, was imported specifically via the TIM22 complex. Similarly, it has been recently reported that human sideroflexins, a class of IMM proteins that contain five transmembrane domains and that do not belong to the SLC25 family, are imported via TIM22 [ 111 ]. Therefore, we can assume that the TIM22 substrate spectrum is less intransigent and contains proteins with paired and non-paired transmembrane domains.…”
Section: Protein Translocationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this report, authors observed that the yeast mitochondrial pyruvate carrier, which has an odd number of transmembrane segments and a matrix-facing N-terminus, was imported specifically via the TIM22 complex. Similarly, it has been recently reported that human sideroflexins, a class of IMM proteins that contain five transmembrane domains and that do not belong to the SLC25 family, are imported via TIM22 [ 111 ]. Therefore, we can assume that the TIM22 substrate spectrum is less intransigent and contains proteins with paired and non-paired transmembrane domains.…”
Section: Protein Translocationmentioning
confidence: 99%
“…Then, ND3, ND6, and ND4L are added to this intermediate. At least two of these assembly factors, namely TMEM126B and NDUFAF1, have been recently reported to be imported in a TIM22-dependent manner [ 111 ].…”
Section: The Respiratory Chain and Supercomplexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, subunits of the mitochondrial pyruvate carrier (MPC) were identified as unconventional TIM22 cargo proteins containing two or three predicted transmembrane spans [ 169 , 170 ]. In addition, sideroflexins (SFXN), which contain five transmembrane segments, were also recently described as cargos of this complex [ 171 ]. The human TIM22 complex is a complex of 440-kDa comprised of TIM22, TIM29, TIM10B, and the lipid kinase AGK [ 165 , 166 , 167 , 168 ].…”
Section: Carrier Translocase Mediated Import Across the Inner Membranementioning
confidence: 99%